How does the school culture of a high school in the Western Cape impact the psychological well-being of a teacher of colour? - Chunderduth, Trisha Nicolle (School of Education, 2025)
The purpose of this study is to examine how the school culture of a high school in the Western Cape impacts the psychological well-being of a woman teacher of colour. This study is situated within an Interpretivist research paradigm, and focuses on an oral narrative case study design via the process of semi-structured interview questions involving one participant – a woman teacher of colour. I examine the research question through the method of Ryff's Model of Psychological well-being. Key findings show that this teacher's interpersonal relationships in the school were fractured along race lines with her principal favouring white teachers to teach subject-specific content. Moreover, personal relationships with her family-sister and husband-proved to be more positive and mitigated the negative effects of some interpersonal relationships in her work environment. In conclusion, this thesis examines how systemic racial and gender biases, coupled with autocratic leadership, adversely affected a woman teacher of colour's psychological well-being in a high school in the Western Cape. Recommendations include a holistic approach regarding policy reform, targeted interventions, and community involvement as essential to improve teacher well-being and, by extension, educational outcomes.